Liquidez dos discursos e contextos emergentes na educação superior no Brasil: a perspectiva das mídias sociais e tecnopolíticas - Mello, Gabriela Barichello (2020)
This Master's in Education research is the result of studies carried out with the Research Line “Educational public policies, educational practices and their interfaces”, of the Graduate Program in Education at the Federal University of Santa Maria. Also, it is linked to the studies developed in the Research Group on Public Policies and Educational Management - GESTAR / CNPq / UFSM, in view of the following problem: What discourses and emerging contexts are related to Higher Education in Brazil, from the perspective of social media and technopolitical? In response to the research problem, the general objective was to “understand the discursive productivity and the emerging contexts in Higher Education in Brazil, from the perspective of social and technopolitical media”. For specific objectives: (i) to recognize in the socio-historical context of globalization, especially XXI, the processes of [re] policy options for Higher Education in Brazil and emerging contexts; (ii) to identify the possible technopolitical meanings and ways of [re] articulation of Higher Education in the production of emerging contexts; (iii) analyze the devices and respective contexts of media transformation, based on their speeches and impacts on the production of meanings about federal universities in Brazil. Methodologically, it presents itself as a qualitative exploratory-interpretative research, using the online search, with a proposal for discourse analysis based on Charadeuaua (2008). Morosini's studies (2014) are used as the theoretical basis; Bauman (2008); Zuboff (20018), Maués (2019), Morozv (2018), among other authors. It is concluded with this study that the evidenced speeches are in inter-relation with the goals and “orientations” of the multilateral organisms towards the privatization of the public Higher Education in Brazil. These new configurations of Emerging Contexts become even more incisive in their processes, becoming an imperative through technologies and their uses that, increasingly, reflect social [dis] control.